In-hospital costs of community-acquired colonization with multidrug-resistant organisms at a German teaching hospital - Sabine Engler-Hüsch; Thomas Heister; Nico T Mutters; Jan Wolff; Klaus Kaier (BMC, 2018)
Abstract Background Antibiotic resistance is a challenge in the management of infectious diseases and can cause substantial cost. Even without the onset of infection, measures must be taken, as patients colonized with multi-drug resistant (MDR) pathogens may transmit the pathogen. We aim to quantify the cost of community-acquired MDR colonizations using routine data from a German teaching hospital. Methods All 2006 cases of documented MDR colonization at hospital admission recorded from 2011 to 2014 are matched to 7917 unexposed controls with the same primary diagnosis. Cases with an onset MDR infection are excluded from the analysis. Routine data on costs per case is analysed for three groups of MDR bacteria: Methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococcus (VRE), and multidrug-resistant gram-negative bacteria (MDR-GN). Multivariate analyses are conducted to adjust for potential confounders. Results After controlling for main diagnosis group, age, sex, and Charlson Comorbidity Index, MDR colonization is associated with substantial additional costs from the healthcare perspective (€1480.9, 95%CI €1286.4-€1675.5). Heterogeneity between pathogens remains. Colonization with MDR-GN leads to the largest cost increase (€1966.0, 95%CI €1634.6-€2297.4), followed by MRSA with €1651.3 (95%CI €1279.1-€2023.6), and VRE with €879.2 (95%CI €604.1-€1154.2). At the same time, MDR-GN is associated with additional reimbursements of €887.8 (95%CI €722.1-€1053.6), i.e. costs associated with MDR-colonization exceed reimbursement. Conclusions Even without the onset of invasive infection, documented MDR-colonization at hospital admission is associated with increased hospital costs, which are not fully covered within the German DRG-based hospital payment system.